HUBUNGAN LAMA PENGGUNAAN KATETER URETRA TERHADAP KEJADIAN INFEKSI SALURAN KEMIH PADA PASIEN YANG TERPASANG KATETER URETRA DI RUMAH SAKIT UMUM DAERAH DELI SERDANG LUBUK PAKAM - Anita Sri Gandaria Purba; Samuel Ginting (Jurnal Penelitian Keperawatan Medik, 2018)
Infection was an incident witch often happened on hospital and can made financial lost for patient, family and the hospital itself. The method of this research was cross secsional use observation pieces instrument of research. The population of the research were the patients on the hospital in Deli Serdang who assembled catheter urethra. The sample was 30 respondents. The result of research indicated that the incident of urethra infection of 30 respondents who assembled catheter urethra, there were 7 persons (23,3%) were not happened the infection and 23 persons (76,7%) got to infection and devided into 2 persons (6,7%) with character urethra ≤ 1-2 days, 16 persons (53,3%) with character urethra 3-5 days and 5 persons (16,7%) with the character very long ≥ 6-7 days. Through of the result of Chi-Square statistics test, was gotten the result pvalue = 0,002, where p Value < 0,05. This was indicated that there was the significant relationship between the time of used catheter urethra to incident of urinary tract infection. According to this result, so to emphasize the incident of urinary tract infention was needed control and replacement the catheter urethra periodicly based on the standart procedure of treatment and prevention of infection